A new species of Cyrtodactylus (Squamata: Gekkonidae) from Ninh Thuan Province, southern Vietnam - Do, Quyen Hanh; Phung, Trung My; Ngo, Hanh Thi; Le, Minh Duc; Ziegler, Thomas; Pham, Cuong The; Nguyen, Truong Quang (Zootaxa, 2021)
A new species of the Cyrtodactylus irregularis group is described from Ninh Thuan Province, southern Vietnam based on molecular divergence and morphological differences. Cyrtodactylus orlovi sp. nov. is distinguished from the remaining Indochinese bent-toed geckos by having the unique combination of the following characters: size medium (SVL 61.0–77.7 mm); dorsal tubercles in 16–20 irregular rows; 36–39 ventral scale rows; precloacal pores absent in females, 5 or 6 in males, in a continuous row; femoral pores absent; 3–8 enlarged femoral scales; postcloacal spurs 1 or 2; lamellae under toe IV 16–19; a continuous neckband; a highly irregular transverse banded dorsal pattern; the absence of transversely enlarged median subcaudal scales. In phylogenetic analyses, the new species was revealed to be the sister taxon to a clade consisting of Cyrtodactylus cattienensis and the most recently described species from Vietnam, C. chungi, with 12.1–12.4% and 11.7 % pairwise genetic divergence from the two species, respectively, based on a fragment of the mitochondrial COI gene.